THE RESEARCH OF EMPATHIC ABILITIES IN PRIMARY SCHOOL CHILDREN AS A STRUCTURAL ELEMENT OF THE CATEGORY “COMPASSION OF THE PUPIL” - Guseva, Victoria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article deals with one aspect of the problems of development compassion in children. It outlines from positions of the system approach are researched empathic abilities of primary school children as one of the structural elements (substructures) in the category “compassion pupil”. The article contains the results of diagnosing the level of empathic abilities of primary school children. We have installed that a child with a developed ability to empathy tends more to the manifestation of gracious behavior and only 14% of primary school children are predisposed to the implementation of the merciful act.The article is intended for a wide range of readers and those, who are interested in pedagogy.